KARAKTERISTIK SEKTOR PERTANIAN DI PROVINSI BALI MENURUT SUBSEKTOR PENYUSUN - ARSANA, PUTU OKA SURYA; SUSILAWATI, MADE; JAYANEGARA, KETUT (E-Jurnal Matematika; Vol 2 No 4 (2013)DO - 10.24843/MTK.2013.v02.i04.p054, 2013)
Bali instead of famous for tourism also popular at agriculture. One of them is subak. It is a culture heritage in the world. To cope with this problem the development in agriculture should be increased. The goal for this research are to know the identifiier factors of agriculture devolopment in Bali, the most dominat factors, and the variable which represent the development of agriculture in Bali. The method of analysis used for this research is factors analysis. Factor analysis is used to reduce the data or summary, for variable which is being changed to a new variable called factor and still load many information contained in a real variable. The method used in the factor analysis is principal component analysis method. Many  factors are determined by eigen values. The  factor rotation which used is varimax rotation. Based on the research results, got seven factors with the diversit ies which can be explained are 76.417%. Factors dryland farming as the most dominant factor identifier with the total value of the largest eigenvalues ??is 4.564 or 25.356% with variables representing these factors are widely planted potatoes and pulses.
Keywords: factor Analysis, principal component analysis, eigen value, factor rotation